Modal analysis for implant stability assessment: Sensitivity of this methodology for different implant designs. Issue 8 (August 2018) - Zanetti, Elisabetta Maria; Ciaramella, Stefano; Calì, Michele; Pascoletti, Giulia; Martorelli, Massimo; Asero, Riccardo; Watts, David C.
Abstract: Objective: To investigate the influence of implant design on the change in the natural frequency of bone-implant system during osseointegration by means of a modal 3D finite element analysis. Methods: Six implants were considered. Solid models were obtained by means of reverse engineering techniques. The mandibular bone geometry was built-up from a CT scan dataset through image segmentation. Each implant was virtually implanted in the mandibular bone. Two different models have been considered, differing in the free length of the mandibular branch ('long branch' and 'short branch') in order to simulate the variability of boundary conditions when performing vibrometric analyses. Modal analyses were carried out for each model, and the first three resonance frequencies were assessed with the respective vibration modes. Results: With reference to the 'long branch' model, the first three modes of vibration are whole bone vibration with minimum displacement of the implant relative to bone, with the exception of the initial condition (1% bone maturation) where the implant is not osseointegrated. By contrast, implant displacements become relevant in the 'short branch' model, unless osseointegration level is beyond 20%. The difference between resonance frequency at whole bone maturation and resonance frequency at 1% bone maturation remained lower than 6.5% for all modes, with the exception of the third mode of vibration in the 'D' implant where this difference reached 9.7%. With reference to the 'short branch', considering the first mode of vibration, 61–68% of the frequency increase was achieved at 10% osseointegration; 72–79% was achieved at 20%; 89–93% was achieved at 50% osseointegration. The pattern of the natural frequency versus the osseointegration level is similar among different modes of vibration. Significance: Resonance frequencies and their trends towards osseointegration level may differ between implant designs, and in different boundary conditions that are related to implant position inside the mandible; tapered implants are the most sensitive to bone maturation levels, small implants have very little sensitivity. Resonance frequencies are less sensitive to bone maturation level beyond 50%.